Labor Crisis and Structural Transformation in the Sragi Sugar Industry during the 1929 Global Economic Depression - Puspa Lestari; Reinelfa Zahra Aurelia; Alvina Nuris Sorayya; Romadi; Dimas Anggoro (UM Purwokerto Press, 2025)
The collapse of global commodity markets during the 1929 economic crisis profoundly affected export-oriented colonial industries, including the sugar sector in the Dutch East Indies. While previous studies have examined the macroeconomic decline of the Javanese sugar industry during the Great Depression, limited attention has been given to how global market shocks reshaped labor conditions and local industrial structures at the factory level. This study investigates the impact of the 1929 global economic crisis on the labor conditions and structural transformation of the Sragi Sugar Factory in Pekalongan Regency during the period 1928–1933. Using historical research methods, the study analyzes colonial statistical reports, archival documents, newspapers, and secondary historical literature through heuristic, source criticism, interpretation, and historiographical synthesis. The findings show that the collapse of global sugar prices, which fell from approximately ƒ14.25 per quintal in 1929 to ƒ3.46 in 1934, triggered drastic production reductions across Java. At the Sragi Sugar Factory, these pressures led to significant structural changes, including production restrictions under the Chadbourne Agreement, declining plantation areas, and workforce reductions exceeding 60 percent. Labor conditions deteriorated through wage cuts of up to 50 percent, the replacement of permanent employment with daily contract labor, and increased economic vulnerability among workers and their families. Beyond immediate labor impacts, the crisis also transformed the regional economic structure as sugarcane cultivation declined and workers shifted toward subsistence agriculture and alternative sectors. This study contributes to the historiography of colonial economic history by demonstrating how global commodity crises reshaped labor relations and industrial organization at the local level within the plantation economy of colonial Java.